Otimização na produção do concentrado proteico de farelo de arroz e utilização na alimentação do jundiá (Rhamdia quelen) - Loureiro, Bruno Bianch (2020)
The present study was carried out with the objective of evaluating the effects of the inclusion of de-oiled and de-phytinized rice bran protein concentrate (DRBPC) on the parameters of growth and performance, metabolic responses (serum and liver), nutrient deposition and digestive enzymes of silver catfish (Rhamdia quelen), fed with diets containing different levels of replacement of protein from fishmeal by DRBPC. For the development and choice of the best DRBPC, obtained from de-oiled and dephytinized rice bran (DDRB), the influence of the DDRB extrusion process on the improvement of the extraction and concentration of the fresh and extruded DDRB protein was tested, obtaining two protein concentrates: DRBPC and DRBPCext. The results obtained indicated that the extrusion process per se or combined with the concentration methodology was not efficient to increase the crude protein (CP) content of the DDRB, presenting lower values (P <0.05) compared to protein concentrate from DRBPC. After obtaining and choosing the concentrate with the highest CP content (42.39%), DRBPC protein was included in different levels (25, 35, 45 and 55%) of fishmeal replacement in silver catfish diets. A biological assay was conducted during 45 experimental days, where 300 silver catfish, with initial body weight 10.28 ± 0.19 g were randomly distributed and allocated in 15 polypropylene tanks (20 fish per tank) with a volume of 100 L connected to a thermo regulated water recirculation system. The fish were fed with experimental diets, three times a day (9 am, 1:30 pm and 5 pm), until apparent satiety. The experimental design was completely randomized with five treatments and three replications. The data were submitted to analysis of variance (ANOVA) and the means compared to the Tukey test (p <0.05). At the end of the experimental period, a decrease in performance was observed (P <0.05) on weight gain, specific growth rate and relative weight gain in fish fed diets containing 45 and 55% of DRBPC inclusion. For total protein deposited, a reduction (P <0.05) was verified in fish that received diets containing 35% or more of the inclusion of DRBPC. The highest activity of the digestive enzyme trypsin was observed in fish fed diet 35% of DRBPC. Based on the results obtained, it was found that the DDRB extrusion process was not efficient to facilitate the extraction of the bran protein by the protein concentration process. The protein concentration carried out from the DDRB in natura, allowed to obtain a concentrate with a higher crude protein content (42.39%). As for the results of the biological test, it was observed that the inclusion of 25% of the DRBPC in replacement of the protein coming from fishmeal did not negatively affect the parameters of growth and metabolic, deposition of nutrients and digestive enzymes of silver catfish (Rhamdia quelen).